PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE DAN DIVIDEND PAYOUT RATIO TERHADAP PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI (Students' Journal of Accounting and Banking, 2014)
This study aims to analyze the extent of the effect of firm size, profitability, financial leverage and dividend payout ratio to income smoothing practices in manufacturing companies listed in Indonesia Stock Exchange. The population in this study are listed Manufacturing Company in Indonesia Stock Exchange in the period of time between the years 2010 - 2012 respectively, amounting to 115 manufacturing companies. The sample used in this study using purposive sampling, in 2010 there were 34 companies, in 2011 there were 32 companies, in 2012 there were 47 companies. Total data obtained as 115 method used in this research is to use a binary logistic regression analysis. The results showed that of the 115 corporate data, there are 34 companies that make the practice of smoothing income, while income smoothing does not practice there are 79 corporate data. Results of logistic regression analysis showed that the size of the company who proxied using total assets, and ROA profitability proxied using income smoothing effect on practice. Financial leverage and dividend payout ratio is never an influence on the practice of income smoothing.Keywords: income smoothing, firm size, profitability, financial leverage and dividend payout ratio